Evaluation of Body Composition in Hemodialysis Thai Patients: Comparison between Two Models of Bioelectrical Impedance Analyzer and Dual-Energy X-Ray Absorptiometry - Kulapong Jayanama; Supanee Putadechakun; Praopilad Srisuwarn; Sakda Arj-Ong Vallibhakara; Prapimporn Chattranukulchai Shantavasinkul; Chanika Sritara; Surasak Kantachuvesiri; Surat Komindr (Journal of Nutrition and Metabolism)
Background. Body composition measurement is very important for early nutritional care in hemodialysis patients. Dual-energy X-ray absorptiometry (DXA) is a gold standard test, but clinically limited. Bioelectrical impedance analysis (BIA) with multifrequency technique is a practical and reliable tool. Objective. This cross-sectional study was aimed to compare the agreement of BIA with DXA in measurement of body composition in hemodialysis patients and to evaluate their associated factors. Methods. Body composition was measured by 2 BIA methods (InBody S10 and InBody 720) and DXA after a hemodialysis session. A total of 69 measurements were included. Pearson’s correlation and Bland and Altman analysis were used to determine the correlation of body composition between methods and to compare the methods agreement, respectively. Results. The correlation coefficients of body compositions were strong between DXA and InBody S10 (fat mass index (FMI): r=0.95, fat-free mass index (FFMI): r=0.78) and also between DXA and InBody 720 (FMI: r=0.96, FFMI: r=0.81). Comparing to DXA, the means of each body composition measured by InBody S10 method were not significantly different in each gender, but differences were found in FM, %FM, and FMI measured by InBody 720. Conclusions. In maintenance hemodialysis patients, the measurement of body composition with DXA and both BIA methods had highly significant correlations; practically, BIA method could be used as an instrument to follow FM and FFM and to measure the edematous stage. Further studies with large populations are warranted.